Poland against the background of Central and Eastern Europe. The statistical portrait of the region - Wyszkowska, Dorota (Polska na tle Europy Środkowej i Wschodniej. Portret statystyczny regionu, 2011)
Central and Eastern Europe is a region of great diversity, both in the economic and social sphere, which stems from the fact that countries belonging to this region have different historical and cultural background, economic resources, social capital, and political systems. Ten of the states at present belong to the EU, which affects significantly both the pace of the changes that are taking place there and their development level. In the last ten years, great economic changes took place there, yet their pace was different. Countries such as Slovenia, Slovakia, and the Czech Republic stand out favourably from other Central and Eastern European countries. Among the countries of this region belonging to the EU, Poland is characterised by lower indices in almost all the fields presented in the work
Ekonomia = Economics, 2011, Nr 2 (14), s. 272-280
Keywords: Central and Easter Europe; development level; diversity of the region